NILAI-NILAI ‘URF DALAM TRADISI BHEN GHIBEN PADA PERKAWINAN MASYARAKAT MADURA DI KELURAHAN SIANTAN TENGAH - Faizah, Amelia; Ardiansyah, Ardiansyah; Zaman, Q. (Al-Usroh, 2025)
This study aims to thoroughly examine the practice of the Bhen Ghiben tradition in marriages among the Madurese community in Siantan Tengah Village, as well as to analyze the embedded 'urf values as part of a local culture that is still preserved to this day. The research was conducted using a qualitative-descriptive approach through field research methods, where primary data were obtained from in-depth interviews with community leaders and cultural practitioners, while secondary data were collected from literature reviews related to the Bhen Ghiben tradition and the concept of 'urf in Islamic law. Data collection techniques included interviews and documentation, while data analysis employed an interactive model encompassing data reduction, data presentation, verification, and conclusion drawing. The results show that the implementation of Bhen Ghiben begins two to three months before the wedding, initiated by a deliberation between families to determine items such as household furniture, clothing, and traditional food. On the wedding day, these items are symbolically handed over by the groom's family to the bride's family. This tradition is not merely a customary obligation, but also contains strong 'urf values, including responsibility, mutual cooperation, mutual respect, and benefit, which together strengthen the social, cultural, and normative structures within the Madurese community of Siantan Tengah.